PENERAPAN VOICE OVER AL DALAM PEMBUATAN KONTEN VIDEO PROPERTI DIGITAL PADA PT DEWE MAKMUR MAPAN - Abdul, Achmad Abdul Ghofur; Pebrianggara, Alshaf Pebrianggara (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2026)
PT Dewe Makmur Mapan faces a major obstacle in the slow production of property video content, which hinders the effectiveness of the company's digital marketing. The implementation of Voice Over (VO) AI technology has become crucial as a strategic solution to achieve cost efficiency and significantly accelerate content production processes. The purpose of this research is to implement VO AI technology to increase audience engagement on various partner digital platforms. The implementation method is carried out thru the integration of artificial intelligence technology into the digital content production workflow, which includes video creation, photography, and visual design, as well as social media management and online property branding strategies. The research results show that there is a reduction in operational production costs and more optimal work time efficiency compared to conventional methods. Additionally, there was an improvement in content performance, evidenced by an increase in the number of viewers on the company's social media platforms. This implementation confirms that adopting AI technology in video production can effectively and economically optimize property marketing strategies in the digital age.